Ritual Terroir: The Generation of Site-Specific Vitality - Chau, Adam Yuet (Archives de sciences sociales des religions, 2021)
The French term "terroir" has entered the English language carrying more or less the same viticultural and culinary references. Despite its close English-language cousin "terrain" and "territory", terroir is a lot more than things having to do with the earth. It is a particular and dynamic "compositional assemblage" (Chau, 2012) of all elements that contribute to the unique qualities of a product (be it wine, foie gras or mushroom): climate, weather, topography, soil, precipitation, drainage, exposure to sunlight (duration, direction, intensity, etc.), disasters, ecology (including flora and fauna), human intervention (e.g. irrigation, fertilisers, weeding, introduction of cultivar and other bio-elements, fermentation and other procedures, craftsmanship and handling), etc. The deliberate, modern-day construction and privileging of terroir is a reaction against "soulless" mass production, against food and drink with no traceable origin because they have been industrially produced (with the help of globally-produced chemical fertilisers and feed), mixed and packaged. I propose to look at the production of power-laden religious sites through the lens of "ritual terroir", using examples from Chinese religious practices (drawn from my own fieldwork). Just like food and drink, some religious practices are extremely translocalisable and, even as they are always adapted to specific local conditions as they spread across the globe (e.g. Zen Buddhism, evangelical Christianity, Tibetan Buddhism, post-colonial and post-Cold-War Islam), many thrive precisely because of a delinking between the practices and any particular site or terroir. On the other hand, some other religious practices are resolutely spatially grounded in the production of specific religious sites and draw spiritual power from these sites. I will present the case of the Dragon King Valley (Longwanggou) in northcentral China to illustrate the workings of ritual terroir. Like all local cults, the reputation and efficacy of the Black Dragon King depend on an ensemble of site-specific features that combine geographical and human input.